Waste disposal - Dorion, Christiane (London : Franklin Watts, 2007)
Examines the careless use of the Earth's natural resources, efforts to encourage recycling of garbage, and ways to safely dispose of industrial waste.
Includes index.
8.9
5-8.
5-8
Keywords: Pollution -- Juvenile literature; Refuse and refuse disposal -- Juvenile literature; Refuse and refuse disposal -- Environmental aspects -- Juvenile literature; Pollution; Refuse and refuse disposal; Refuse and refuse disposal -- Environmental aspects; Pollution; Refuse and refuse disposal; Refuse and refuse disposal -- Environmental aspects